Investigating The Impact Of Nurse Staffing Ratios On Patient Safety Outcomes In Hospital Settings (Journal of Namibian Studies : History Politics Culture, 2022)
Adequate nurse staffing is crucial for patient safety, yet optimal ratios remain debated. This mixed methods study examined the impacts of differing nurse-patient ratios on safety outcomes across 165 inpatient units at 15 Saudi hospitals. Staffing and outcome data were analyzed for relationships to identify thresholds influencing falls, infections, ulcers, and satisfaction. Units with ratios ≥1:4 showed significantly lower adverse events versus those with ≥1:5 ratios. Interviews with 25 nurses described unsafe workloads, burnout, and rationing of care below 1:4 staffing. Integrated results suggest ratios between 1:3 to 1:4 optimize safety balanced with costs. Findings can inform minimum mandated staffing levels and acuity-based adjustments to improve Saudi patient outcomes. Nurse perspectives highlighted the need to address understaffing while pursuing wider safety reforms.